Composition of the Survival Motor Neuron (SMN) Complex in Drosophila melanogaster. - Matera, A.G.; Raimer, A.C.; Schmidt, C.A.; Kelly, J.A.; Droby, G.N.; Baillat, D.; Ten Have, S.; Lamond, A.I.; Wagner, E.J.; Gray, K.M. (G3 : genes - genomes - genetics, 2019)
Spinal Muscular Atrophy (SMA) is caused by homozygous mutations in the human survival motor neuron 1 (SMN1) gene. SMN protein has a well-characterized role in the biogenesis of small nuclear ribonucleoproteins (snRNPs), core components of the spliceosome. SMN is part of an oligomeric complex with core binding partners, collectively called Gemins. Biochemical and cell biological studies demonstrate that certain Gemins are required for proper snRNP assembly and transport. However, the precise functions of most Gemins are unknown. To gain a deeper understanding of the SMN complex in the context of metazoan evolution, we investigated its composition in Drosophila melanogaster Using transgenic flies that exclusively express Flag-tagged SMN from its native promoter, we previously found that Gemin2, Gemin3, Gemin5, and all nine classical Sm proteins, including Lsm10 and Lsm11, co-purify with SMN. Here, we show that CG2941 is also highly enriched in the pulldown. Reciprocal co-immunoprecipitation reveals that epitope-tagged CG2941 interacts with endogenous SMN in Schneider2 cells. Bioinformatic comparisons show that CG2941 shares sequence and structural similarity with metazoan Gemin4. Additional analysis shows that three other genes (CG14164, CG31950 and CG2371) are not orthologous to Gemins 6-7-8, respectively, as previously suggested. In D.melanogaster, CG2941 is located within an evolutionarily recent genomic triplication with two other nearly identical paralogous genes (CG32783 and CG32786). RNAi-mediated knockdown of CG2941 and its two close paralogs reveals that Gemin4 is essential for organismal viability.